Synthesis, inactivation, and localization of extracellular and intracellular Escherichia coli hemolysins. - Oropeza-Wekerle, R L (1989)
Extra- and intracellular Escherichia coli hemolysin expressed by two cloned hly determinants, both under the control of the activator element hlyR, were analyzed. One determinant carried all four hly genes (hlyC, hlyA, hlyB, and hlyD), whereas the other carried only the two genes (hlyC and hlyA) required for synthesis of active hemolysin but not those essential for its secretion. It was shown that the total amounts of HlyA protein and of hemolytic activity are similar in both cases in logarithmically growing cultures. The E. coli strain carrying the complete hly determinant released most hemolysin into the media and accumulated very little HlyA intracellularly. The active extracellular hemolysin (HlyA*) was inactivated in the stationary phase without degradation of the HlyA protein. In contrast, the hemolysin which accumulated intracellularly in the E. coli strain carrying hlyA and hlyC only was proteolytically degraded at the end of the logarithmic growth phase. Immunogold labeling indicates that active intracellular HlyA bound preferentially to the inner membrane, whereas that part of the extracellular HlyA which remained cell-bound was located exclusively at the cell surface. It was shown by fluorescence-activated cell sorter analysis that active extra- and intracellular HlyA* bound with similar efficiency to erythrocytes, whereas hemolytically inactive HlyA protein did not bind to these target cells.